The Role of Educational Institutions in Community Empowerment to Improve Community Welfare - Wulan Budi Astuti (Journal of Islamic Economy and Community Engagement, 2022)
Social action internship for advanced university students is a community service activity in certain areas or educational institutions, carried out in groups, preferably non-physical activities in the field of education. Social action internship for advanced university students aims to provide real work experience in the field in the field of forming an independent attitude and responsibility in carrying out work in the field. In addition, social action internship for advanced university students also aims to help the community increase the level of knowledge and skills so that it is expected to improve their welfare. The social action internship for advanced university students is divided into four stages of activity, namely debriefing, implementing activities on site, compiling reports, and assessing. The implementation of the social action internship for advanced university students in Jatirejo Village, Gunungpati District, Semarang City. The work program in Jatirejo Village is a program that emphasizes the theme of the Role of Students in Community Empowerment to Improve Welfare. The physical program of the social action internship group for advanced university students in Jatirejo Village, among others: planting toga plant seeds, making banana satay and marketing, distributing masks, making processed fruit and fro, helping the community in preparing rice every Friday.Keywords: Community Empowerment, Welfare, toga plant